The Syntax of Null Possessors with Kinship Terms and Body Part Nouns in Vietnamese - Andrew Simpson; Linh Pham (Languages)
Bare nouns representing kinship terms (KNs) and body parts (BPNs) can be assumed to project a null possessor argument, which allows for the interpretation of such nouns relative to other linguistically present NPs. In Vietnamese, the distribution of KNs and BPNs is subject to different locality conditions and leads to the analysis of null possessors with KNs as covert anaphors, while null possessors with BPNs are null pronominals (pro). This contrasts with Mandarin Chinese, where it has been suggested that null possessors of KNs and BPNs are two different types of null anaphors. The observed distributional differences and analyses of bare KNs and BPNs in Vietnamese vs. Chinese raise questions of parametric variation with regard to null elements with parallel interpretive properties and also whether linking mechanisms may occur with other bare nouns without the projection of null possessors that are subject to binding theoretic locality restrictions.